Self care in Oman: public and healthcare professional perspectives - Al Juma, Muna A. (2017)
Self care and self-medication are a vital component of modern healthcare. Pharmacists can play an important role in supporting people’s self care of minor ailments, from advising on self care and supplying non-prescription medicines to identifying the need for GP referral. The available literature about self care and the role of community pharmacists in Oman is scarce. A knowledge gap was identified in areas related to people’s experiences of self care and self-medication, and how they utilise the healthcare services available when responding to their minor ailments. It is also not clear how and when the public utilise community pharmacy or how pharmacists contribute to patient care within the primary care setting. This study aims to identify the factors that influence the self care of minor ailments in Oman by exploring the perceptions of the public and healthcare professionals. A qualitative approach was used to answer the research question. Two groups of subjects were interviewed: people recruited from public places e.g. shopping centres (phase one), and pharmacy staff and general practitioners working within primary care (phase two). The pharmacy staff and general practitioners were recruited from both the public and private health sectors. Data were collected using semi-structured face-to-face interviews. The data was analysed thematically using the principles of constructivist grounded theory. Data management and analysis were performed using NVivo, a qualitative data analysis software. Results from the two phases were triangulated to provide a better understanding about the factors influencing self care of minor ailments in Oman. Individual interviews were conducted with 21 members of public, 14 general practitioners and 17 pharmacy staff. Three main themes were identified that influenced the self care of minor ailments in the Omani health system: individual knowledge, beliefs and attitudes; communication and relationships; and the healthcare system. Individual factors that were identified to influence the public illness behaviour and the healthcare professionals’ approach to manage minor ailments were: attitudes to medicines; understanding of self care and minor ailments; and attitudes to self-medication. Attitudes to pharmacy staff; poor communication and language barriers; and interprofessional relationships had an impact on supporting self care and accessing the community pharmacy for advice. Role responsibilities; standard and quality of practice; and information support and health literacy were the three health-system-related factors that influenced self care of minor ailments. This research represents the first holistic understanding of the factors that influence self care and management of minor ailments in Oman, including the opportunities and challenges for the pharmacy profession in providing patient care. This conceptual model could help in adapting a comprehensive approach to effectively address factors related to optimising the self care of minor ailments and improve utilisation of healthcare services. The three main themes influencing self care in Oman have highlighted a number of important implications for future practice and research to improve primary healthcare provision and the role of pharmacy profession in patient care.